2015
DOI: 10.3897/natureconservation.11.4424
|View full text |Cite
|
Sign up to set email alerts
|

The BioREGIO Carpathians project: aims, methodology and results from the “Continuity and Connectivity” analysis

Abstract: BioREGIO Carpathians is a transnational cooperation project, co-financed under the second call of the EU South East Europe Transnational Cooperation Programme, priority area "Protection and Improvement of the Environment". BioREGIO Carpathians run for three years (2011)(2012)(2013) and is a flagship project for the Carpathian Convention (article four dealing with landscape and biological diversity), its Biodiversity Protocol and the Biodiversity Working Group. The project is built on the conservation, restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…By examining the multi-species corridors, we observed that the Carpathian Mountains are the most likely landscape unit where these linkages can be created with great success. The Carpathians are a well-known hot spot for biodiversity in Europe 86 , with large continuous natural areas 87 , and projects involving connectivity in the Carpathians have been developed in recent years 88 . Areas along the Danube River also showed great connectivity, where almost continuous corridors between SCIs were obtained (more so for amphibians than reptiles).…”
Section: Discussionmentioning
confidence: 99%
“…By examining the multi-species corridors, we observed that the Carpathian Mountains are the most likely landscape unit where these linkages can be created with great success. The Carpathians are a well-known hot spot for biodiversity in Europe 86 , with large continuous natural areas 87 , and projects involving connectivity in the Carpathians have been developed in recent years 88 . Areas along the Danube River also showed great connectivity, where almost continuous corridors between SCIs were obtained (more so for amphibians than reptiles).…”
Section: Discussionmentioning
confidence: 99%
“…It was conducted with the Linkage Mapper Toolset and its Linkage Pathways Tool (LinkageMapper.org). The LCP represents the route along which the least resistance -imposed by the landscape matrix on the general wildlife movements -occurs (Favilli et al, 2015). The LCP identi es the route of least cumulative resistance for a species moving between two SACA1 areas (McRae and Kavanagh 2012; Jones, 2015; Beier, 2018; Cayton 2019).…”
Section: De Nition Of Ecological Linkages and The Identi Cation Of Be...mentioning
confidence: 99%
“…This would serve as a foundation for de ning the actions on the ground that might facilitate both the dispersal of individuals within a species among natural areas and human-wildlife coexistence, thus identifying the potential socioeconomic bene ts for the given territories and local inhabitants. We selected a structural connectivity approach in the project area, and avoided concentrating on functional connectivity (as in Taylor et al, 1993Taylor et al, , 2006Favilli et al, 2015), which describes an organism's behavioural response to both the landscape structure and the landscape matrix. The structural connectivity analysis has a more holistic approach and describes the physical relationships and permeability between habitat patches (Hilty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Weights used for each habitat factor and each layer. The figure also presents the final weights obtained by choosing the weighted geometric mean (data processed after [35][36][37]). For the land cover categories, a different number of weights was used (four and five categories), considering that in Season 2 and Season 4 (spring and autumn, with five categories) the brown bear has a larger area of movement, due to its needs (see Table 4) (our contribution on the basis of [36]).…”
Section: R6: Map Of the Ecological Network For Brown Bear At The Leve...mentioning
confidence: 99%